2009
DOI: 10.1575/1912/3047
|View full text |Cite
|
Sign up to set email alerts
|

Forward sound propagation around seamounts : application of acoustic models to the Kermit-Roosevelt and Elvis seamounts

Abstract: The Basin Acoustic Seamount Scattering Experiment (BASSEX) of 2004 was conducted to measure forward-scattering around the Kermit-Roosevelt Seamount Complex in the Northeast Pacific. The BASSEX experiment was focused on the bathymetric effects on acoustic propagation, in particular, on direct blockage, horizontal refraction, diffraction, and scattering by the seamounts. A towed hydrophone array, with 64 sensors cut for 250Hz (3m spacing), was used to measure the signals transmitted from the aforementioned broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The results showed that the TL increased up to about 15 dB because the deep refracted waves would be blocked by the seamount, and the shadowing loss behind seamount was an f 1/2 dependence at frequencies greater than 50 Hz. Kim studied the mechanisms of sound propagation around seamounts [6]. The BAS-SEX experiment carried out in the Northeast Pacific around the Kermit Roosevelt seamounts in 2004 measured the broadband pulses and found that the convergence and shadow zones behind the seamounts were matched well between the experiment data and 3D sound propagation model results.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results showed that the TL increased up to about 15 dB because the deep refracted waves would be blocked by the seamount, and the shadowing loss behind seamount was an f 1/2 dependence at frequencies greater than 50 Hz. Kim studied the mechanisms of sound propagation around seamounts [6]. The BAS-SEX experiment carried out in the Northeast Pacific around the Kermit Roosevelt seamounts in 2004 measured the broadband pulses and found that the convergence and shadow zones behind the seamounts were matched well between the experiment data and 3D sound propagation model results.…”
Section: Introductionmentioning
confidence: 94%
“…Since the effects of seamounts are complex and the efficiency of numerical methods is usually low, previous studies on the sound propagation of seamounts mostly used 2D or N×2D models. With the deepening of ocean acoustics research, the focus gradually shifted to research about the 3D sound propagation phenomena of seamounts [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Physical experiments and theoretical approaches have been explored over the past several decades. Reference [5] studied the mechanisms of sound propagation around seamounts. The BASSEX experiment carried out in the Northeast Pacific around the Kermit Roosevelt seamounts in 2004 measured the broadband pulses and found that the convergence and shadow zones behind the seamounts were matched well between the experiment data and three-dimensional sound propagation model results.…”
Section: Introductionmentioning
confidence: 99%
“…As the lower boundary of the underwater acoustic field, the seabed bathymetry has a significant influence on acoustic propagation, which is critical for signal level (S) estimation of high precision. There have been many related studies on the effect of bathymetry on acoustic propagation [1][2][3][4][5][6][7][8][9][10][11][12]. Weston proposed the concept of horizontal refraction and found that the sloping bottom and seamount would cause strong horizontal refraction effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…Weston proposed the concept of horizontal refraction and found that the sloping bottom and seamount would cause strong horizontal refraction effects [6]. Kim used the data obtained from the BASSEX to study the problem of acoustic propagation around seamounts, in particular, direct blockage, horizontal refraction, diffraction, and scattering by the seamounts, and verified the existence of horizontal refraction [7]. Li et al found that seamounts could cause three-dimensional acoustic horizontal refraction [8] [9].…”
Section: Introductionmentioning
confidence: 99%